Factors Related To The Incidence Of Diarrhea In Toddlers In The Coastal Area Of Kuala Lempuing Health Center Working Area, Bengkulu City - Theresia Hanna Marsita Uli; Jipri Suyanto; Retni Retni (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Intoduction: Diarrhea is one of the global health problems that remains a serious challenge, especially in developing countries including Indonesia. According to data from WHO and UNICEF (2023), approximately 2 billion cases of diarrhea occur each year worldwide. Of this number, around 1.7 billion cases result in more than 525,000 deaths of toddlers each year. About 78% of toddler deaths due to diarrhea occur in Africa and Southeast Asia. Method: This study used a quantitative approach with a cross-sectional design. A sample of 92 respondents was selected through simple random sampling. The instruments used were observation, and analysis was conducted using the Chi-Square test. Result and Discussion: The univariate analysis showed that 52 respondents had poor water pH, with 30 respondents (32.6%) having acidic water, and 22 respondents (23.9%) having alkaline water containing microbes. Additionally, 37 respondents (40.2%) had poor physical water conditions, and 43 respondents (46.7%) experienced diarrhea. The bivariate analysis indicated a significant relationship between water pH (p=0.005), the presence of microbes (p=0.003), and the physical condition of the water (p=0.005) with the incidence of diarrhea. These findings suggest that water pH, the presence of microbes, and water physical conditions are factors that can influence the occurrence of diarrhea. Conclusion: The researchers recommend that the health center monitor more frequently and enhance surveys, as well as provide education regarding the environment and water that causes diarrhea. It is also hoped that the community will periodically improve their. home environment and maintain the cleanliness of water sources.